A high‐resolution anorectal manometry parameter based on integrated pressurized volume: A study based on 204 male patients with constipation and 26 controls. Issue 9 (24th May 2018) - Seo, M.; Joo, S.; Jung, K. W.; Lee, J.; Lee, H. J.; Soh, J. S.; Yoon, I. J.; Koo, H. S.; Seo, S. Y.; Kim, D.; Hwang, S. W.; Park, S. H.; et al.
Abstract: Background: Conventional anorectal manometric parameters based on linear waves cannot properly predict balloon expulsion (BE) time. We aimed to determine the correlation between integrated pressurized volume (IPV) parameters during simulated evacuation (SE) and BE time in healthy individuals and constipated patients and to assess the correlation between each parameter and symptoms. Methods: A total of 230 male participants (including 26 healthy volunteers and 204 chronically constipated patients) underwent high‐resolution anorectal manometry (HRAM) and BE tests. The IPV was calculated by multiplying the amplitude, distance, and time from the HRAM profile. Receiver operating characteristic curve (ROC) analysis and partial least square regression (PLSR) were performed. Key Results: ROC analysis indicated that the IPV ratio between the upper 1 cm and lower 4 cm of the anal canal was more effective for predicting BE time (area under the curve [AUC]: 0.74, 95% confidence interval [CI]: 0.67‐0.80, P < .01) than the conventional anorectal parameters, including defecation index and rectoanal gradient (AUC: 0.60, 95% CI: 0.52‐0.67, P = .01). PLSR analysis of a linear combination of IPV parameters yielded an AUC of 0.79. Moreover, the IPV ratio showed a greater clinical correlation with patient symptoms than conventional parameters. Conclusions and Inferences: The IPV parameters and the combination of IPV parameters via PLSR were more significantly correlated with BE time than the conventional parameters. Thus, this study presents a useful diagnostic tool for the evaluation of pathophysiologic abnormalities in dyssynergic defecation using IPV and BE time. Abstract : The novel integrated pressurized volume (IPV) parameters and the combination of IPV parameters via partial least square regression were more significantly correlated with balloon expulsion (BE) time than the conventional parameters. IPV parameters can be useful diagnostic tools for the evaluation of pathophysiologic abnormalities in dyssynergic defecation using high‐resolution anorectal manometry and BE tests.